Experimental study on construction tension and local component failure of double inner and outer latticed shell string structure. Issue 4 (April 2017) - Yao, Yun-long; Ma, Guang-ying; Dong, Shi-lin; Bai, Guang-bo; Liu, Hong-chuang
The roof system of Yueqing Gymnasium adopts a new hybrid space structure called the double inner and outer latticed shell string structure. The prestressing construction of this structure is complex. Thus, the whole process analysis for the pretensioning scheme and cable breaking should be performed prior to construction. The tension processes and effects of local component failures were studied on the basis of the structural model test. The effects of the construction sequences of the inner inclined cables and outer radial cables were tested, and the effects of the tensioned outer radial cables were investigated. The analysis and test results show that the internal forces and structural deformations vary linearly during the construction tension processes, and that the structural configuration is stable. The structure can be tensioned to the designed configuration successfully with reasonable construction sequences and programs. Finally, the local component failures of the test model were studied, and the effects of the cable, strut, and sling breakings on structural performance in different positions were discussed. The test results of the cable and strut breaking show that the double inner and outer latticed shell string structure has excellent structural rigidity and has a certain capability for resisting progressive collapse.